Mostre. Alla ricerca di una definizione - Lanzarini, Orietta; Turrini, Davide (Opus Incertum, 2024)
The exhibition project, inherently in a state of constant evolution, demonstrates a remarkable capacity to interpret diverse instances (social, artistic, economic, and political) while integrating stimuli from different disciplinary domains. In the investigated period, running from 1951 to 1992, exhibitions emerged as pivotal protagonists of both the cultural and social stage, prompting exhibition designers and curators to develop innovative strategies of communication. Following this red thread, the essays collected in the following sections explore exhibition design through three main perspectives: analytical, experimental, and authorial. The first section examines the representation, within the exhibition space, of prominent historical figures, artistic and documentary material, as well as the openness to social themes and cultural practices. The second section explores, through selected international experiences, diverse approaches to transcending disciplinary boundaries, fostering new forms of dialogue with audiences. Finally, the third section and the Delizie degli eruditi investigate some exemplary ‘authorial exhibitions’, where the architectural language of the authors is interwoven with the specific demands of exhibition design. Finally, the Atlante – Ritratto di una mostra section illustrates, through a sequence of photographs, an exemplary exhibition experience.